Minimally Invasive Redo Mitral Valve Replacement using a Robotic-Assisted Approach. Issue 5 (September 2017) - Patel, Hetal; Lewis, T. P. Clifton; Stephens, Richard L.; Angelillo, Margaret; Sibley, David H.
Minimally invasive, robotic-assisted cardiac surgery has been shown to decrease transfusion rates, decrease wound infection rates, shorten hospital length of stay, and allow for a faster return to full activity compared with traditional sternotomy approaches. However, its application has chiefly been limited to primary, isolated procedures such as primary mitral valve repair or replacement. We describe the first reported use of a robotic surgery platform to perform reoperative mitral valve replacement using a minimally invasive, totally endoscopic, port-access approach.